Failure Is an Option: Impediments to Short Selling and Options Prices - Evans, Richard B.; Geczy, Christopher C.; Musto, David K.; Reed, Adam V. (Review of Financial Studies, 2009)
Regulations allow market makers to short sell without borrowing stock, and the transactions of a major options market maker show that in most hard-to-borrow situations, it chooses not to borrow and instead fails to deliver stock to its buyers. A part of the value of failing passes through to options prices: when failing is cheaper than borrowing, the relation between borrowing costs and options prices is significantly weaker. The remaining value is profit to the market maker, and its ability to profit despite competition between market makers appears to result from the cost advantage of larger market makers.